Penerapan Model Pintar Memilih Jajanan Yang Sehat (PMJS) Bagi Siswa di SDIT Darul Hasan Kota Padangsidimpuan Sebagai Upaya Pencegahan Kasus Cuci Darah Anak - Nasution, Dina Rahmi Solihad; Silitonga, Yusnita Wahyuni; Hasibuan, Elmi Sariani (Universitas Aufa Royhan Di Kota Padangsidipuan, 2025)
Children, with their curiosity and tendency to follow their peers, often pay little attention to the cleanliness or quality of the food they consume. This habit, if left unchecked, can have a negative impact on long-term health, one of the worst impacts that can arise is the case of dialysis, which is currently experiencing an increase in cases in children. The purpose of this activity is to correct children's bad snacking habits and to improve children's health which has recently given rise to dialysis cases by implementing the PMJS (Pintar Memilih Jajanan Yang Sehat; Smart Choosing Healthy Snacks) model. The implementation began with socialization to SDIT Darul Hasan Grade 4 pupils regarding daily balanced nutrition patterns. The second activity was the implementation of training on selecting snacks according to the PMJS model that has been explained in the socialization stage. Next is the mentoring and evaluation of the implementation of PMJS and ends with the sustainability of the program by ensuring that sufficient knowledge has been provided as the expected end result. From the results of this community service activity, a positive impact was obtained in the form of increased pupil knowledge of healthy snacks and more selective when buying snacks.